The Effects of Austempered and Quenched & Tempered on Mechanical Properties of Alloyed Grey Cast Iron - Abdullah, Bulan; Yusof, Khalissah; Zamri, Farahnini; Hayati Saad, Nor (International Journal of Engineering and Technology, 2018)
In this study, the effects of austempered and quenched & tempered on mechanical properties of grey cast iron with and without the addition of niobium were investigated. The austempering heat treatment started by heating the samples to an austenitizing temperature of 900°C with a soaking time of 90 minutes before quenched in salt bath furnace with a temperature of 360°C and hold for 180 minutes before it been cooled down to room temperature. The quench and tempering process started with heating the samples at 910°C and hold for 33 minutes. Then the samples are quenched by using engine oil before being heated up again to temperature of 400°C with soak time up to 17 minutes before allow it to be cooled at room temperature. The tests conducted include hardness, tensile and impact test. The microstructure of the samples was observed using optical microscope. The fracture surface of the test tensile and impact specimens was analyzed by using S.E.M. observation. The hardness of the as-cast, austempered and quenched & tempered alloyed grey cast iron are higher compared to the hardness of pure grey cast iron. By addition of Niobium, the tensile strength of the grey cast iron increased by 67.49 % compared to pure grey iron. Tensile strength and elongation of the alloyed grey cast iron slightly increased after heat treated. Austempered alloyed grey cast iron resulted the highest value of impact toughness (6.5 J) compared to other specimens. This showed that austempered alloy grey cast iron is the best in absorbing the energy subjected to it.
Keywords: Austempered Grey Iron; Fractography; Mechanical Properties; Quenching and Tempering.